(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Intelligence is the general ability to study and solve problems that embody all the cognitive abilities of a person: to feel, perceive, remember, describe, think, imagine. Artificial intelligence is a separate field of Informatics, usually concerned with the possibilities associated with the human mind: understanding the language, teaching, discussing, solving the issue, translating and creating computer systems with similar capabilities. Artificial intelligence (SI) allows computers to learn about their experiences, adapt to the parameters given, and perform tasks that were previously only possible for humans. In this article, opinions and reflections on artificial intelligence and it technologies will be discussed.